Weight Loss By Soil Burial Degradation Of Green Natural Rubber Vulcanizates Modified By Tapioca Starch - Mazlan, Mazliah; Mohamad, Noraiham; Ab Maulod, Hairul Effendy; Abd Razak, Jeefferie; Othman, Intan Sharhida; Hashim, Hanizam; Mohd Abid, Mohd Asyadi 'Azam; Ahsan, Qumrul; Mohd Safeai, Nur Maizatul Nadia; Mohd Mef’at, H. (Centre For Advanced Research On Energy (CARe), 2017)

(untitled)
The weight loss of soil degraded natural rubber vulcanizates modified by tapioca starch was investigated. The samples were prepared by melt compounding using a Haake internal mixer at different tapioca starch loading of 0, 5, 10, 20, 40, and 60 phr. The samples were exposed to soil burial testing for duration of 7, 14, 21 and 28 days. Then, the weight loss was measured using the difference in weight before and after the testing. The mass reduction was observed to be proportionately increased with the increment of tapioca starch loadings and prolonged soil burial duration. The rate of degradations observed was supported with morphological characteristics of the vulcanizates. This study is highly significant towards the development of green natural rubber composites by incorporation of tapioca starch.